2015
DOI: 10.3892/or.2015.4281
|View full text |Cite
|
Sign up to set email alerts
|

Malignant transformation of host stromal fibroblasts derived from the bone marrow traced in a dual-color fluorescence xenograft tumor model

Abstract: Abstract. Solid tumors are abnormal tissues containing tumor and non-tumor cells, also known as tumor stromal cells. However, the malignant potential of tumor stromal cells remains largely unknown. The aim of the present study was to investigate the malignant potential of host bone marrow-derived stroma cells in transplanted subcutaneous tumors of the glioma stem/progenitor cells (GSPCs) labeled using the dual-color fluorescent tracer technique. The previously established human glioma stem/progenitor cell line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 53 publications
1
11
0
Order By: Relevance
“…With a fluorescent tracer xenograft model based on the inbred nude mice that express EGFP extensively, including in brain tissue, our work focused on TME research has confirmed that some host mesenchymal cells have undergone malignant transformation. In the present as well as our previous reports, 12,20,21 we found that some fibroblasts, bone marrow‐derived dendritic cells and oligodendrocytes in transplanted tumor microenvironmentwere malignant transformation induced by primary transplanted tumor cells. The Foxn1 nu .B6‐Tg(CAG‐EGFP) mice auricle transplantation model could also facilitate research on the tumor immune microenvironment in vivo, with a two‐photon fluorescence microscope.…”
Section: Discussionsupporting
confidence: 88%
“…With a fluorescent tracer xenograft model based on the inbred nude mice that express EGFP extensively, including in brain tissue, our work focused on TME research has confirmed that some host mesenchymal cells have undergone malignant transformation. In the present as well as our previous reports, 12,20,21 we found that some fibroblasts, bone marrow‐derived dendritic cells and oligodendrocytes in transplanted tumor microenvironmentwere malignant transformation induced by primary transplanted tumor cells. The Foxn1 nu .B6‐Tg(CAG‐EGFP) mice auricle transplantation model could also facilitate research on the tumor immune microenvironment in vivo, with a two‐photon fluorescence microscope.…”
Section: Discussionsupporting
confidence: 88%
“…#7500, CA, USA). Similar to previously reported methods 36 , GSC23 cells were transfected with red fluorescence protein (RFP) gene, and hMSCs were transfected with green fluorescence protein (GFP) gene. In another method, GSC23 cells were also transfected with a lentiviral vector GV348 (sequence element: Ubi-MCS-SV40-puromycin) containing LOXP-STOP-LOXP-RFP gene, and MSCs were transfected with a lentiviral vector GV348 containing a CRE enzyme gene.…”
Section: Methodsmentioning
confidence: 99%
“…Informed consent was obtained from the patient prior to sample acquisition.SU3 cells were regularly authenticated on the basis of morphology, expression of CD133 and nestin, sphere formation ability and tumorigenicity and were regularly examined for (absence of) mycoplasma by Mycoplasma Stain Assay Kit (Beotime, China). SU3 cells were transfected with the RFP gene using a lentiviral-mediated gene transfection kit (GeneChem, Shanghai, China) [6], and cultured in stem cell medium. Briefly, 20 ng/ml bFGF, 20 ng/ml EGF and 1 × B27 supplement were added to DMEM/F12.…”
Section: Methodsmentioning
confidence: 99%